Medicine Masks of the Iroquois People as Revealed by the False Faces Society - Niesyto, Josef (Studia Etnologiczne i Antropologiczne, 2020)
Present-day Iroquois are seeking to preserve traditional healing methods. Members of the False Faces Society routinely perform cleansing rituals using Hodo masks. The spiritual significance and proceedings of the rituals were conveyed by the employees of the Iroquois community center (Longhouse) and the fellow tribesmen gathered around these centers. The participants provided information on the ways of acquiring, crafting, invoking, storage, and honoring the sanctified, animated artifact – the mask. The author of the article confronts the current position of the Onondaga Reserve and the Grand River Reserve Iroquois with historical teachings. The elder generation of Indians has maintained their faith in the mystical power of the rituals, while the secularized new generation approaches them with a strong skepticism.